Significance of parents’ involvement, cultural religious values, gender role and family teaching values in relation to children’s personality development and their educational achievements in Punjab Province, Pakistan - Khurram Shehzad; Dr. Farah Riaz; Prof. Dr. Muhammad Iqbal Zafar* (Journal of Religion and Society, 2025)
This study is significant as it examines how family relationships influence children’s personality development and educational achievement within Punjab Province, Pakistan. The primary objective is to investigate the effects of parental involvement, cultural and religious values, gender roles, and demographic factors (age, level of education, occupation, and parental education) on children’s academic performance and psychosocial outcomes. The study employs a quantitative research design using structured questionnaires administered to 450 school and college going students across urban and rural districts of Punjab. Data were analyzed through descriptive statistics to identify patterns and relationships among variables. The analysis revealed that parental involvement, supportive cultural and religious practices, and equitable gender role attitudes positively predict children’s self-esteem, motivation, and academic success, while economic hardship and traditional patriarchal constraints limit development. Key findings highlight that higher parental education, family cohesion, and active engagement are strongly associated with enhanced personality development and educational outcomes. The study recommends policy interventions, parent education programs, and school-family partnerships that promote inclusive, culturally sensitive, and gender-equitable parenting to foster holistic child growth in Punjab. Keywords: Family relationships, child development, parental Involvement, educational achievement.